Preliminary Analysis of Wind Power in 4 Colombian Cities, and Utilization Estimates with Urban Wind Turbines - León Vargas, Fabian; Krejci, Edwing; García Jaramillo, Maira (TECCIENCIA, 2016)
Wind power generates a significant percentage of electricity and is used by a great many countries, including the largest producers worldwide: China, the United States, Germany and Spain. Colombia has a wind energy potential of an estimated 21 GW on its Atlantic coast alone, and yet in the nation as a whole only 19.5 MW are currently generated, coming from the Jeripachi wind farm in La Guajira. The utilization of this type of energy in other geographical locations is still undeveloped, sparking a need to evaluate its utility and profitability, such as in urban generation and consumption. In this paper we present the preliminary results of a study on the estimation of wind power in 4 cities, where weather stations have been set up at University Antonio Nariño installations. We measured variables such as wind speed, wind direction and environmental temperature .As a result, we statistically characterized wind speed in each location by fitting the data to a Weibull distribution. We also estimated the percentage of energy coverage that could be exploited in an average home using a domestic urban wind turbine. The study also presents a prefeasibility analysis of what could be expected from investment in self-generated electricity using such technology in the studied locations.